STRATEGI PENGEMBANGAN INDUSTRI GULA KELAPA DI KABUPATEN PURBALINGGA, JAWA TENGAH - Fadilla, Arif (Jurnal AGRISEP, 2021)
Purbalingga Regency has great potential for the development of the coconut sugar industry.  This development effort is expected to improve product competitiveness and as a prime mover for overall industrial development.  For this reason, this research aims to determine the strategy for developing the coconut sugar industry in Purbalingga Regency. This research uses descriptive analysis method, with data collection techniques through observation and in-depth interviews. The results of the analysis show various strategies for the development of the coconut sugar industry. The steps that can be taken are those related to strengthening the institution, human resources, as well as process and product development. All these steps are completed with integration of supply and marketing networks, and improving infrastructure.